Non-isoflavones Diet Incurred Metabolic Modifications Induced by Constipation in Rats via Targeting Gut Microbiota - Liu, Jialin; Chang, Ruirui; Zhang, Xiaobei; Wang, Zhongzhao; Wen, Jun; Zhou, Tingting (Frontiers in Microbiology, 2018)
Isoflavones, presenting in leguminous plants and the normal chow diet, are known to alter intestinal microbiota, yet their deficiency has not been widely studied for its effect on constipation in biochemical state of rats. Our previous study discovered the differences in pharmacokinetic traits of isoflavones from Semen sojae praeparatum fed with normal chow diet (ISO) and non-isoflavones diet (NISO). To gain insight into the key role of intestinal microbiota in constipation and metabolic differences caused by isoflavones deficiency, we observed a significant decrease in fecal pellet numbers, fecal water content, intestinal transit rate together with the serum concentrations of substance P (SP) and vasoactive intestinal peptide (VIP) in NISO group, compared with those in the ISO group. Following 16S rRNA compositional sequencing, results excluded the changes in intestinal microbiota over time and highlighted that a total of 5 phyla and 21 genera changed significantly, among which Firmicutes, Bacteroidetes, Blautia, Prevotella, Lactobacillus and Bifidobacterium were closely related to constipation. In addition, Lactobacillus, produceing β-glucosidase which contribute to biotransform glycosides into aglycons and exert the bioactivities consequently, was decreased after non-isoflavones diet intake. Meanwhile, predicted metagenomics indicated that the pathway of glycan biosynthesis and metabolism was markedly down-regulated after non-isoflavones diet intake. Taken together, the findings suggested that the changes in the dietary components could alter the biochemical state of rats, which may be triggered by the abnormal modifications facilitated by β-glucosidase-producing bacteria. Our study shed a new strategy to explore the relationship among disease phenotypes (D), intestinal microbiota (I), enzymes (E) and traits of metabolism (T) named as “DIET,” which can provide a reference for further study of the mechanism in regulation of intestinal bacteria-mediated diet on diseases.